Pengabdian Kepada Masyarakat Melalui Kegiatan Sosial, Pendidikan, Dan Kesehatan Di Desa Pasir Gala, Kabupaten Lawe Bulan, Kabupaten Aceh Tenggara - Marsya, Jiwa Malem (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service in the form of social service carried out by the health team together with the education team of Gunung Leuser University lecturers and the Social Service Team of Southeast Aceh Regency provided tremendous benefits to the community of Pasir Gala Village, Lawe Bulan District, Southeast Aceh Regency. The activities included socialization on the prevention of underage marriage, maternal and child health education, drug abuse education, and education. The purpose of conducting these activities is to provide health and education services, as well as social service, to the community in order to achieve community well-being in the fields of health and education, and to enhance social awareness and concern among fellow human beings. The activity was held on August 20, 2025, involving the Head of Women's Protection and Children's Rights Fulfillment of DINSOSP2KBP3A, as well as education by lecturers from Gunung Leuser University and medical personnel such as sub-district midwife coordinators and nurses. A total of 90 participants attended, consisting of 15 people for the socialization of preventing underage marriage, 35 participants in maternal and child health education, and 25 participants in DINSOS and NAPZA education at SMPN 1 Lawe Sigala-gala, along with 15 lecturers from Gunung Leuser University.